اسهامات تنقيب البيانات في تنمية القطاعات الاقتصادية بين الفرص والتحديات - بن الضب, عبد الله; طواهير, عبد الجليل (University of Eloued جامعة الوادي, 2022)
This research aims to show the importance of data mining as the first component of big data, In addition, it is a modern administrative entrance interested in exploring knowledge in databases on the other hand, which has become of great interest to most economic sectors at the international level, which helps to build and analyze future forecasts in the field of decision-making. One of the most important results of this study is to show the different stages of big data mining and to identify the most important challenges; Big data mining remains complex in light of heterogeneous data, with the difficulty of balancing data quality and maintaining privacy.
The contribution of data mining to the development of economic sectors opportunities & challenges
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: تنقيب البيانات؛ بيانات ضهة ة؛ تنةية؛ قطاعات اقتصادية; data mining; big data; development; economic sectors.